Finite Element Analysis of Crane Hook and Optimization Using Taguchi Approach - Bhatkar, Omkar P.; Javir, Arun V.; Ashok, Shinde Ajay; Sumant, Sawant Subodh; Eknath, Ukarde Suraj; Shivram, Kavathankar Kunal (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2015)
A Crane hook is a device for grabbing and lifting loads of heavy duty by mean of a device such as crane hoist. A crane hook is usually equipped with a safety latch to prevent the disengagement of the lifting rope to which the load is being attach. The CAD model of a lifting crane hook is initially prepared from the Analytical Design. In the present report crane hook of trapezoidal section is modeled using UG-NX 8.0, further, importing the CAD model into ANSYS 15.0 we estimate until 20 tones i.e. equivalent to 200000N load to be gradually applied, eventually we observed the von-misses stress developed in the model by FEM method these results von-misses stresses are being compared with Taguchi L9 orthogonal array for specific results. Thus, these results would lead us to determine various stresses and deflections in the designed CAD model. In order to reach the most optimum model from different materials of hook would be tested and the most efficient material would be selected.